La quercia da sughero (Quercus suber L.) nel Salento: analisi diacronica e sinfitosociologica (Adriatico Meridionale, Italia) - Beccarisi, L.; Biondi, E.; Casavecchia, S. (Fitosociologia, 2010)
Subject of this article is the study of the residual woods of cork oak (Quercus suber L.) in the southern part of the Puglia region, which in the area find their eastern distribution limit in Europe. They are survivors of a more extensive forest formations occupying the plain near the city of Brindisi and some areas in the territory of Ostuni. Of these are presented the environmental conditions in which they are and the historical analysis of their variation in the time, deduced by analyzing literature from the early nineteenth century. The diachronic analysis of their distribution is presented in maps at 1:25000 scale. The analysis of plant communities present in the investigated area, were carried out by the sinphytosociological method that led to recognize the communities that are connected in relation to the serial dynamics, to these forests belonging to the association of Carici halleranae-Quercetum suberis of which the new subassociation arbutetosum unedonis is described and the subassociation typus is explained. This is a post- fire shrub attributed to the new association Calicotomo infestae-Phillyreetum mediae characterized by Phillyrea media, Calicotome infesta and Pyrus amygdaliformis which are in dynamic relationship with the forest subassociation of arbutetosum unedonis of Carici halleranaeQuercetum suberis while to the subassociation caricetosum halleranae binds the more mesophilous shrub described with the new association Rhamno alaterni-Pyretum amygdaliformis.
Keywords: diachronic analysis; Quercus suber; southern italy; synphytosociology